Mobilising capital for emerging markets what can structured finance contribute? - Köhn, Doris; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Is structured finance dead? Many have asked this question after the financial crisis. Or is structured finance ?evil? and therefore should it be dead? This book suggests neither nor. Even if structured finance can be misused or applied under inappropriate conditions, it can also be an effective tool for reaching development objectives. The authors in this volume focus on the potential of structured finance in the aftermath of the financial crisis. They explore the conditions under which structured finance is suitable for emerging markets highlighting both its benefits and risks. The book combines professional and scientific perspectives and points towards various useful applications of structured finance in support of small and medium-sized enterprises and microfinance. This also includes activities as diverse as infrastructure development, remittances, rural livelihood, and Shari?ah-compliant Islamic finance. Private investors are far more perseverant and willing to take on risks than many believe. Private capital could serve to provide the scale necessary to reach the Millennium Development Goals. Preeti Sinha, World Economic Forum The current market crisis teaches us that it is important to work by exact standards and that nothing stays as it is; therefore we need to uphold sound practices in the structuring of development finance transactions. André Laude, IFC The microfinance industry always wanted to get integrated into the capital market. Now it actually happened and it turns out as a twilight zone. It is important therefore to keep in mind for what purpose structured finance is done and establish incentives to focus on the right clients. Alexia Latortue, CGAP Securitisation will help the microfinance industry to allocate capital to where it is needed. Edgardo Salomón Barredo, Financiera Finsol (México) In the future we will see more local, down-market and refined forms of structured development finance transactions. Jack Lowe, Blue Orchard Fina
Securitization: Wonder Drug or Financial Alchemy?.- Mobilising Capital for the Poor - How Does Structured Finance Fit in Emerging Markets?.- The Role of Public and Private Investors for Structured Finance in Emerging Markets.- Structured Finance - Mobilising New Means to Attract Capital.- Mobilising Structured Finance for Development - Potential Welfare Benefits and Challenges of Securitisations in Large Emerging Markets.- Structured Finance for Development - Outlook for New Applications.- Shari'ah Compliant Structured Finance - Characteristics, Analogies and Legal Risks in Common Law Jurisdictions.- Securitization of Worker Remittances.- Structured Finance Approaches to Livelihood Projects in India.- The Use of Structured Finance for a Deposit Based MSME Banking Group in Emerging Markets - The Case of ProCredit.- Using the Toolbox - Solutions in Customizing Structured Finance.- Microcredit as an Asset Class: Structured Microfinance.
Electronic reproduction.
Keywords: Corporations -- Finance -- Developing countries; Electronic book